Bridging soft skills and work readiness: The strategic role of self-efficacy and organizational experience in final-year students - Kristiana, Julia; Syamsuddin, Achmad; Giovanni, Jonathan; Meitiana, Meitiana; Lampe, Normand Armando (JSM: Jurnal Sains Manajemen, 2025)
In today’s increasingly dynamic labor market, final-year university students are required to possess more than just academic achievements to ensure a successful transition into the workforce. However, recent observations indicate that many students are inadequately prepared, with limited experience and underdeveloped soft skills. This study aims to examine the influence of soft skills and organizational experience on the work readiness of final-year students at the University of Palangka Raya, with self-efficacy as a mediating variable. Utilizing a quantitative explanatory approach, the study involved 100 final-year students selected through purposive sampling. Data were collected via closed-ended questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings reveal that both soft skills and organizational experience have a positive and significant effect on self-efficacy. However, neither of these variables has a direct significant effect on job readiness. Instead, self-efficacy plays a crucial mediating role, significantly linking soft skills and organizational experience to job readiness. This indicates that confidence in one’s ability is a central factor in preparing students for employment. Based on these findings, it is recommended that universities strengthen experiential learning and soft skills development programs, with a particular emphasis on enhancing students’ self-efficacy. Integrating training, mentoring, and real-world experiences into academic curricula can improve students’ transition into professional environments and better align graduate competencies with labor market demands.